PENGEMBANGAN MEDIA KONVERSI ENERGI ANGIN MENJADI ENERGI LISTRIK - lisa mustika (Jurnal Pendidikan Fisika dan Sains, 2020)
This study aims to determine the working principle of the media for the conversion of wind energy into electrical energy and to test the feasibility of the media to convert wind energy into electrical energy which will be used as a learning medium on energy conversion material. This research uses the Research and Development (R&D) development method and the development model used is 4D. In the 4D Model, the activities carried out at each stage of media development are the defining stage (Define), the design stage (Development), the development stage (Develop), and the dissemination stage (Disseminate), but in this study carried out only to the validation stage only and did not reach the stage of dissemination (implementation). The working principle of the conversion media of wind energy into electrical energy is by converting a kinetic energy from the air into mechanical energy which causes the rotation that occurs on the generator to produce an electric current. Wind energy is used to spin the blades so that the rotor rotates, when the rotor rotates, the generator will automatically flow electrical energy. The results of media validation carried out by media experts to see the percentage of the feasibility of the media conversion of wind energy into electrical energy as a whole is 60%, which means that this media is quite feasible to be used in learning media. As for the results of the overall material validation carried out by material experts in the media of the conversion of wind energy into electrical energy is 80%, which means that the material in this media is suitable for use in learning.